Konflik dalam Tim Mahasiswa Guru Internship [Conflict Within a Team During Their Student Teaching Internship] - Yanuard Putro DwiKristanto (Universitas Pelita Harapan, 2017)
Conflict within a team of student teachers during their internship is one problem that needs to be managed and overcome in order to make their performance better. Student teachers are expected to establish good communication and resolve conflicts wisely. The subjects of this study were six student teachers who had internships in a YSKI school in Semarang from July to November 2016. This study used a qualitative descriptive approach. Data were collected through observation, interviews and documentation. The results are presented in descriptive narration to explain the conflict and how it was resolved.BAHASA INDONESIA ABSTRAK: Konflik dalam tim mahasiswa guru internship merupakan salah satu masalah yang dapat harus dikelola dan diatasi agar tidak meluas dan mengganggu kinerja mereka dalam praktek mengajar di sekolah. Mahasiswa guru diharapkan dapat membangun komunikasi yang baik dan menyelesaikan konflik dengan bijaksana. Subyek penelitian ini adalah enam mahasiswa guru yang melakukan internship di sekolah YSKI Semarang periode Juli-November 2016. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Hasilnya disajikan secara deskriptif narasi menjelaskan terjadinya konflik dan mengatasinya.